2011
DOI: 10.1016/j.gaceta.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Secuelas de la violencia colectiva: hablan las víctimas del estudio ISAVIC

Abstract: The qualitative results of this study are coherent with those obtained through the parametric phase of the ISAVIC study and provide a more complete overview of the nature of the sequelae of collective violence and its impact on quality of life. These results should be verified in larger studies and the influence of the social context on the relationship between collective violence and health should be analyzed in greater depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
2
0
3
Order By: Relevance
“…Although “belief in a just world” (Lerner, 1980; Lerner & Simmons, 1966) can help the larger public feel safer by identifying a victim as blameworthy, doing so derogates victims. Consistent with our findings, Larizgoitia, Izarzugaza, and Markez (2009) found that Basque victims of ETA felt alone, stigmatizated, and experienced institutional support as insufficient. This suggests the need for governmental policies that could provide supportive resources to help victims of political violence recover from difficult and traumatic experiences (cf.…”
Section: Discussionsupporting
confidence: 91%
“…Although “belief in a just world” (Lerner, 1980; Lerner & Simmons, 1966) can help the larger public feel safer by identifying a victim as blameworthy, doing so derogates victims. Consistent with our findings, Larizgoitia, Izarzugaza, and Markez (2009) found that Basque victims of ETA felt alone, stigmatizated, and experienced institutional support as insufficient. This suggests the need for governmental policies that could provide supportive resources to help victims of political violence recover from difficult and traumatic experiences (cf.…”
Section: Discussionsupporting
confidence: 91%
“…Esas coacciones han conllevado serias restricciones de la libertad y de la seguridad de la persona directamente afectada, de los familiares o de sus bienes. Según Larizgoitia et al (2009) los efectos en los amenazados y víctimas que han sufrido las mencionadas conductas hostiles, como coacciones de manera continuada, señalan un sufrimiento perpetuo, una angustia intensa, una ansiedad extrema y un sentimiento de persecución. Así pues, mediante las acciones de intimidación y los atentados realizados por ETA, se pretende que las personas amenazadas comprendan que si no cooperan con la organización terrorista pueden sufrir las mismas consecuencias que otras víctimas anteriores, disuadiendo de esta forma a la población vasca de que realice ciertas actividades (De la Calle y Sánchez-Cuenca, 2004).…”
Section: Discussionunclassified
“…Una de las consecuencias de la amenaza y la violencia es que muchas víctimas y amenazados por ETA necesitan la utilización de escolta o guardaespaldas en Euskadi y Navarra. Además, existen diversos efectos negativos que inciden en el ámbito psicológico y social del individuo cuando éste se encuentra bajo amenaza y con necesidad de protección (Echeburúa, 2004;Larizgoitia et al, 2009;Nijdam, Olff, de Vries, Martens y Gersons, 2008;Martin-Peña, Rodriguez-Carballeira, Escartín, Porrúa y Olff, 2011;Pereira, 2004).…”
Section: Las Víctimas De La Violencia Aplicada Por El Entramado De Et...unclassified
“…both the general population as well as those from other groups) as a way of achieving certain political, economic or social objectives. It includes all aggressions and extortions resulting from war, terrorism, ethnic, religious or similar conflicts, gang and mafia organisations, and other organised collectives against other groups, civilian or military (Larizgoitia et al 2011a). Regarding people who suffer from these forms of violence, a distinction can be made between "primary victims" (i.e.…”
Section: Collective Violence In Post-conflict Contexts: the Case Of The Basque Countrymentioning
confidence: 99%
“…As it could be expected, collective violence has also had a psychological and health impact. A study with victims in the Basque Country showed the effects on health and social relations many years after the trauma (Larizgoitia et al 2011a(Larizgoitia et al , 2011b. In this report, several interviews were conducted with 36 primary victims -19 suffered the murder of a close relative, 10 survived attacks and other actions, 7 were subjected to repeated threats and extortionand a population-based survey (N = 2000).…”
Section: Collective Violence In Post-conflict Contexts: the Case Of The Basque Countrymentioning
confidence: 99%